2014
DOI: 10.3354/meps10945
|View full text |Cite
|
Sign up to set email alerts
|

Seabird diet changes in northern Hudson Bay, 1981-2013, reflect the availability of schooling prey

Abstract: Ongoing climate change is altering Arctic marine ecosystems with major consequences for food-webs. Seabirds, by foraging over large marine areas but returning regularly to their breeding colonies, provide a good medium for tracking such changes. We studied the prey delivered to nestling thick-billed murres Uria lomvia at a colony in northern Hudson Bay, Canada, over the period 1981−2013. During that period, ice conditions in the region altered substantially, with earlier break-up and clearance. This change was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Based on multi-decadal time series, we showed that snow petrel body condition at fledging and juvenile survival were related to SIC and large-scale Antarctic atmospheric circulation. In the Arctic, sea ice conditions are known to affect diet of marine predators, and since sympagic fishes are expected to lose habitat due to sea ice decrease, this will affect their predators like seabirds and marine mammals [21].…”
Section: Discussionmentioning
confidence: 99%
“…Based on multi-decadal time series, we showed that snow petrel body condition at fledging and juvenile survival were related to SIC and large-scale Antarctic atmospheric circulation. In the Arctic, sea ice conditions are known to affect diet of marine predators, and since sympagic fishes are expected to lose habitat due to sea ice decrease, this will affect their predators like seabirds and marine mammals [21].…”
Section: Discussionmentioning
confidence: 99%
“…Many surface feeding seabirds forage in the pelagic ecosystem and can therefore act as bioindicators of changes in pelagic communities. Diet samples collected from these birds can be used as ecosystem data from locations that are otherwise difficult to access 14 16 . Black-legged kittiwakes ( Rissa tridactyla , Linnaeus 1758), referred to as “kittiwakes” hereafter, are small colonial gulls with a circumpolar distribution and especially well-suited for such studies.…”
Section: Introductionmentioning
confidence: 99%
“…79° N 12° E), a glacially-influenced fjord on the west coast of Spitsbergen, kittiwakes exhibit relatively predictable foraging behavior during the breeding period and almost all feeding occurs within the fjord 19 – 21 . Consequently, the incubation and chick-rearing diet of kittiwakes in Kongsfjorden primarily reflects prey availability within the fjord, and, thus, the composition of diet samples may be used as an indicator of ecosystem changes in this area 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Guillemot chick diet varies geographically (Barrett , Wilhelm & Storey , Gaston & Elliott ), with Sandeels being more important in northern British colonies than southern colonies (Heubeck , Anderson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have recently attempted to collect data from different studies and different time periods to explore geographical and temporal relationships in prey composition. This can generate large, often heterogeneous datasets which may contain gaps, primarily because some years are unrepresented due to variable effort, different methodology and different sampling frequencies (Gaston & Elliott , Green et al . ).…”
mentioning
confidence: 99%